A Model for the Neurospora Circadian Clock - François, Paul (The Biophysical Society, 2005)
Circadian clocks are important biological oscillators that generally involve two feedback loops. Here, we propose a new model for the Neurospora crassa circadian clock. First, we model its main negative feedback loop, including only experimentally well-documented reactions, the transcriptional activation of frequency (frq) by the white-collar complex (WCC), and the post-transcriptional dimerization of FRQ with WCC. This main loop is sufficient for oscillations and a similar one lies at the core of almost all known circadian clocks. Second, the model is refined to include the less characterized enhancement of white-collar 1 (WC-1) protein synthesis by FRQ, the positive second feedback loop. Numerical testing of different hypotheses led us to propose that the synthesis of WC-1 is enhanced by FRQ monomers and repressed by FRQ dimers. We demonstrate that this second loop contributes significantly to the robustness of the oscillator period against parameter variation. A phase response curve to light pulses is also computed and agrees well with experiments. On a general level, our results show that explicit time delays are not required for sustained oscillations but that it is crucial to take into account mRNA dynamics and protein-protein interactions.